Traditional Domestic Markets and Marketing Systems for Agricultural Products - Dorward, Andrew (Washington, DC: World Bank, 2012)
Market systems play a major role in vibrant economies as mechanisms for exchange (necessary for specialization and economic growth) and for the coordination of that exchange (through price signals which shape producer and consumer incentives in supply and demand). This paper examines the major types of marketing systems linking producers and consumers of domestically consumed agricultural products (cereals, roots and tubers, livestock products, and fruit and vegetables). For each, the major characteristics of supply and demand that affect market structures and prospects for growth in domestic demand being supplied by domestic smallholder farmers are discussed.